2014
DOI: 10.1016/j.pscychresns.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex volume and intrinsic religiosity in non-clinical psychosis

Abstract: Research indicates that religiosity plays a complex role in mental illness. Despite this link, little work has been done to clarify the role of religiosity in persons exhibiting non-clinical psychosis (NCP, individuals experiencing fleeting psychotic-like symptoms in the absence of a formal psychotic disorder). Further, there are no NCP investigations into whether abnormalities exist in brain structures that are associated with religiosity. Understanding these relationships in NCP is important to clarify the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…However, previous studies have found no significant differences in the frequency of experiences between students and general communities (e.g., Lincoln and Keller, 2008 ), or between individuals residing in countries of a similar socioeconomic standing (McGrath et al, 2015 ). One exception is religious beliefs, which are associated with a higher prevalence of hallucinatory phenomena (Pelletier-Baldelli et al, 2014 ; Steenhuis et al, 2016 ). Although of interest, exploring such factors was outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found no significant differences in the frequency of experiences between students and general communities (e.g., Lincoln and Keller, 2008 ), or between individuals residing in countries of a similar socioeconomic standing (McGrath et al, 2015 ). One exception is religious beliefs, which are associated with a higher prevalence of hallucinatory phenomena (Pelletier-Baldelli et al, 2014 ; Steenhuis et al, 2016 ). Although of interest, exploring such factors was outside the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of papers have employed structural magnetic resonance imaging (sMRI) techniques to assess individual differences in gray matter (GM) volume, and thickness. Decreased GM volume has been reported in the frontal and temporal lobes including the pars orbitalis and rostral middle frontal cortex [102], the lateral and medial orbital frontal cortex [103], the inferior temporal gyrus [104], and the left and right putamen [105], with decreased cortical thickness observed in temporal regions [119]. However, there have also been reports of increased volume and thickness, with Jacobsen and colleagues [104], reporting larger GM volume in middle and superior temporal gyri, the angular gyrus, and orbitofrontal cortex in at-risk children, and Cordova-Palomera and colleagues [106] showing relationships between symptom scores with cortical thickness that varied based on season of birth, an environmental risk factor.…”
Section: Neuroimagingmentioning
confidence: 99%
“…The most common clinical method for ascertainment of subclinical samples for imaging appears to be the CAPE [103, 105, 106, 109, 110,]. However, other methods such as structured clinical interviews and scales focused on specific symptom domains have also been employed.…”
Section: Neuroimagingmentioning
confidence: 99%
“…In individuals experiencing fleeting psychotic-like symptoms in the absence of a formal psychotic disorder, elevated intrinsic religiosity was accompanied with volume reductions at the lateral and medial orbitofrontal cortex. Albeit not significant, an inverse link was found between negative psychotic-like symptoms and intrinsic religiosity [58].…”
Section: Discussionmentioning
confidence: 67%